Extra‐striatal dopamine in Parkinson's disease with rapid eye movement sleep behavior disorder. Issue 4 (20th January 2021) - Valli, Mikaeel; Cho, Sang Soo; Masellis, Mario; Chen, Robert; Koshimori, Yuko; Diez‐Cirarda, Maria; Mihaescu, Alexander; Christopher, Leigh; Strafella, Antonio P.
Abstract: Rapid eye movement sleep behavior disorder (RBD) is a common condition found in more than 50% of the patients with Parkinson's disease (PD). Molecular imaging shows that PD with RBD (PD‐RBD+) have lower striatal dopamine transporter activity within the caudate and putamen relative to PD without RBD (PD‐RBD−). However, the characterization of the extra‐striatal dopamine within the mesocortical and mesolimbic pathways remains unknown. We aim to elucidate this with PET imaging in 15 PD‐RBD+ and 15 PD‐RBD− patients, while having 15 age‐matched healthy controls (HC). Each participant underwent a single PET scan with [ 11 C]FLB‐457 to detect the D2 receptor availability within the extra‐striatal regions of interest (ROI), including the prefrontal, temporal, and limbic areas. [ 11 C]FLB‐457 retention was expressed as the nondisplaceable binding potential. Our results reveal that relative to HC, PD‐RBD+ and PD‐RBD− patients have lower levels of D2 receptor availability within the uncus parahippocampus, superior, lateral, and inferior temporal cortex. PD‐RBD+ showed steep decline in D2 receptors within the left uncus parahippocampus with increasing disease severity, but this was not observed for PD‐RBD− patients. Findings imply that extra‐striatal dopaminergic system may play a role in contributing to symptomatic progress in PD patients with RBD. However, validation with more advanced PD patients are needed. Abstract : This PET study characterized D2 receptor (D2R) availability within extra‐striatal regions in Parkinson's disease (PD) patients with (+) and without (−) REM sleep behavior disorder (RBD). With disease progression, only PD‐RBD+ patients showed steep decline in D2R availability within the left uncus parahippocampus. Beyond the striatum, extra‐striatal dopaminergic system may also contribute to PD‐RBD in advanced stages.